Why and how can religions and traditions be plausible and credible in public ethics today? - Müller, Denis (Ethical theory and moral practice, 2001)
This article presents and discusses the meaning of a possible foundation of ethics, both from a philosophical perspective and with regard to religious representations. It proposes to enlarge the conception of rationality in order to take into account the critical contribution of cultures, traditions and religions to an ethics of reconstruction. This also entails rethinking the role of theological ethics and seeking to make more explicit the cultural plausibility and the practical credibility of Christianity in public ethics today.